2015
DOI: 10.1017/ice.2015.77
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Healthcare-Associated Pneumonia with Oral Care in Individuals Without Mechanical Ventilation: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: This analysis suggests a preventive effect of oral care on pneumonia in nonventilated individuals. This effect, however, should be interpreted with caution due to risk of bias in the included trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 32 publications
0
72
0
5
Order By: Relevance
“…As the oral cavity is in contact with the lower airways of the trachea, the oral secretion causes the transfer of colonized bacteria in the mouth to the lower airways, which results in infection and pneumonia (8,9). The results of the current study showed that lack of adequate care of the mouth leads to dry mucosa of the mouth, reduced salivary flow, inflammation of the oral mucosa, and colonization of pathogenic bacteria in the mouth and oropharynx (10,11).…”
Section: Introductionmentioning
confidence: 72%
“…As the oral cavity is in contact with the lower airways of the trachea, the oral secretion causes the transfer of colonized bacteria in the mouth to the lower airways, which results in infection and pneumonia (8,9). The results of the current study showed that lack of adequate care of the mouth leads to dry mucosa of the mouth, reduced salivary flow, inflammation of the oral mucosa, and colonization of pathogenic bacteria in the mouth and oropharynx (10,11).…”
Section: Introductionmentioning
confidence: 72%
“…In addition to the aggravation of periodontal disease, there is a bidirectional causality between some diseases of the oral cavity and systemic morbidities, such as cardiovascular and respiratory diseases 11,13,[25][26] . The presence of oral biofilm in these patients could trigger an inflammatory response, causing a significant increase in the quantity of immunoglobulin and circulating chemical mediators of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This scenario is true for many hospitals 27-29 , both public 2-4 and private 3,8 , due to the scarcity of trained professionals able to get involved in promoting oral healthcare. The training of professionals is a successful practice for reducing infections acquired in hospitals, because they prevent the accumulation of bacterial biofilm and the development of periodontal diseases [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations